FINNISH RIGHT TO BE -CITIZENS INITIATIVE CAMPAIGN AND THE “FEELING OF BEING COUNTED" - Vähäpassi, Valo (AoIR Selected Papers of Internet Research, 2021)
In this paper, I address the Finnish Oikeus olla- (Right to Be) citizens initiative campaign (2021) for a new trans law. I address the online campaign from the point of view of affect, especially the “feeling of being counted” (Coleman 2013; Papacharissi 2015, 25), in several senses. Through media autoetnography and qualitative content analysis of online material, I address the campaign as the experience of becoming part in the counted people, who come to politically matter. Following Sara Ahmed (Smitchz and Ahmed 2014, 1), I do not separate affect from feeling and emotion. Following scholars interested in the meanings and emotions attached with numbers in the current culture (Kennedy and Hill 2018), and the importance of emotions in politics (Coleman 2013; Papacharissi 2015), I am interested in how meanings and emotion are attached to numbers in LGBTIQ politics and activism. I concentrate on the affective aspects of taking part in the initiative and engaging with the online campaign. In this paper, I ask, what work online signature count and the growing figures shared online do, when combined with the discourses and action frames of the campaign? How are the anticipation of reaching the required 50 000, following the increasing count, and reaching the threshold of required amount of signatures, lived and shared online?